Potential of razor clam (Ambal) as coagulant in water treatment process - Amirul, Adenan. (Universiti Malaysia Sarawak, UNIMAS, 2009)
The objective of this research was to determine the feasibility of using chitosan that was extracted from razor clam (ambal) crustacean shells as a natural coagulant to remove the turbidity in water treatment process . This chitosan coagulant was studied in order to solve the pollutant problem that was obtained by the sludge treated by a lum backfill into the environment . Th e sludge and the water treated by this conventional coagulant containing Al 3+ can pollute d the river and induce many diseases . The chitosan has being chosen as an alternative to th is problem due to its neutrality , non toxic material and 100% biodegradable resources. In this study , the process ha s been divided into two parts which were chitosan extraction process and the determination of coagulant optimum dosage process through the jar test experiment. In the jar test , the 150 to 180 NTU turbidity range of Muara Tuang River have been used to determine the effectiveness of using chitosan and aluminum sulphate coagulant in turbidity removed. From the result, the optimum dosage determined and the percentage of the turbidity removed by both coagulants are almost similar. The 40 mg/L concentration chitosan coagulants manage to remove 99.39 % turbidity and the 37.5 mg/L of a lum manage to remove 99.37% turbidity . From th e result, it can conclude that the chitosan extracted from razor clam crustacean shell can be applied as coagulant in water treatment process.